THE EFFECT OF FUEL PREHEATING ON THE PERFORMANCE OF USED OIL FUEL STOVES - Sudarno, Sudarno; Fadelan, Fadelan; Setyatinika, Wisnu Aji; Winardi, Yoyok (Journal of Applied Engineering Science, 2024)
This research explores the utilization of used oil as an alternative fuel and investigates the impact of preheating on its performance in combustion chambers. The study employs an experimental approach to vary preheating methods, utilizing two models: a ring placed in the combustion chamber and a ring combined with a spiral between the inner and outer stove walls. A comparative analysis is conducted against conventional stoves. The investigation focuses on efficiency and flame temperature distribution. Results reveal that the stove incorporating the spiral-ring preheating model demonstrates the highest efficiency at 55.52%, marking a 9.76% increase over conventional stoves. Additionally, this model generates the largest average heat area and the highest temperatures, notably reaching 1077°C, with a broader area above 1000°C compared to other models. The preheating process aids in reducing fuel viscosity and enhancing evaporation, facilitating a more homogeneous air-fuel mixture, thereby promoting more complete combustion.